Design and development of an industrial network laboratory - Leão, Celina Pinto (2011)
This paper presents the first developments of an industrial network laboratory prototype. In the Automation Laboratory several kits have been implemented for local and remote control tests. The approach includes the design and implementation of an industrial network where the common communications protocols can be tested: the Automation Network Locker (ANL). To facilitate the monitoring and control of the network, WALC (Web Assisted Laboratory for Control Engineering on-line Education) interface platform was developed. This allows the remote monitoring and control of the pedagogic kits to complement the teaching/learning automation to undergraduate engineering students. The security of network access is also taken into account in order to limit and control the number of users that can access it. An on-line questionnaire accessed at the end of each semester, allows an actualization and to follow the students’ feedback